PEMBERIAN PENDIDIKAN KESEHATAAN TENTANG SADARI PADA WUS - Ayu Andera, Neta; Lailaturohmah, Lailaturohmah; Restiya Agustin, Erda (Stikes Yarsi Mataram, 2025)
The high incidence of breast cancer in women is often caused by a lack of public understanding of the early detection of the disease. Therefore, health education about breast self-examination (SADARI) is provided to the public, especially women of childbearing age (WUS), to facilitate understanding related to the dangers of breast cancer. This program aims to reduce the incidence of breast cancer in Village Pikatan through counseling and education about SADARI. The method used is to provide health education in the form of direct counseling on the importance of early detection with SADARI to reduce the incidence of breast cancer in WUS. The results of this program showed that most of the 30 respondents had good knowledge about breast cancer and early detection, which was reflected in the positive attitude towards SADARI's behavior. In conclusion, it is hoped that Puskesmas officers can continue to supervise the implementation of SADARI periodically to increase the effectiveness of breast cancer prevention in the community